Tensile Strength Characteristics of Concrete Blocks Using Abaca Fiber - Tampi, Reiner; Don Kabo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The role of concrete as a material to strengthen buildings with long-term durability is an important goal of construction. Abaca fiber has the potential to strengthen concrete network materials. The purpose of this study was to identify the tensile strength characteristics of concrete using abaca fiber. The method used is through experimental studies in the laboratory to test the tensile strength of concrete blocks. This research was carried out in the Materials and Structures Laboratory using five stages. The results of this research have found that the potential of abaca fiber as a binder for cylindrical concrete aggregates with a certain fiber length and fiber volume allows the concrete to be stronger and have high resistance compared to ordinary concrete. In the split tensile strength section, the results obtained show that abaca fiber concrete provides stronger resistance than ordinary concrete if the fiber length is 50mm high and the fiber volume is at 0.15%. The same results are shown in the flexural strength of the beam without reinforcement, namely concrete with abaca fiber has strong toughness if the fiber length content used is 50mm and the fiber volume is at 0.15%. Overall, abaca fiber is very influential on the resistance of concrete if the fiber length and fiber volume are at a certain point, namely 50mm and 0.15%